2022
DOI: 10.3389/fped.2022.1022738
|View full text |Cite
|
Sign up to set email alerts
|

Weight loss in adolescents with down syndrome compared to adolescents with other intellectual disabilities enrolled in an 18-month randomized weight management trial

Abstract: BackgroundThere is limited information on the efficacy of weight management interventions in adolescents with Down Syndrome (DS)ObjectiveTo compare weight change and intervention compliance between adolescents with DS compared to adolescents with non-DS related intellectual disabilities (ID) who were enrolled in an 18-month weight management trial.MethodsParticipants were adolescents (13–21 years) with mild to moderate ID and overweight or obesity. Participants were randomized in a 1:1:1 allocation to one of 3… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 35 publications
(42 reference statements)
0
1
0
Order By: Relevance
“…The few studies available were mainly focused on aerobic capacity assessment [ 11 , 12 , 13 , 14 , 18 ]. Collectively, these studies confirmed that adults with DS have low physical fitness levels and are at increased risk for several co-occurring diseases (such as obesity and diabetes), which are known to benefit from increased PA [ 2 , 13 , 19 , 20 ]. The determinants of PA levels and motor capacities related to physical fitness in adults with DS are poorly studied.…”
Section: Introductionmentioning
confidence: 69%
“…The few studies available were mainly focused on aerobic capacity assessment [ 11 , 12 , 13 , 14 , 18 ]. Collectively, these studies confirmed that adults with DS have low physical fitness levels and are at increased risk for several co-occurring diseases (such as obesity and diabetes), which are known to benefit from increased PA [ 2 , 13 , 19 , 20 ]. The determinants of PA levels and motor capacities related to physical fitness in adults with DS are poorly studied.…”
Section: Introductionmentioning
confidence: 69%